RMBase v2.0: deciphering the map of RNA modifications from epitranscriptome sequencing data. Issue Volume 46:Issue D1(2018) (10th October 2017) - Xuan, Jia-Jia; Sun, Wen-Ju; Lin, Peng-Hui; Zhou, Ke-Ren; Liu, Shun; Zheng, Ling-Ling; Qu, Liang-Hu; Yang, Jian-Hua
Abstract: More than 100 distinct chemical modifications to RNA have been characterized so far. However, the prevalence, mechanisms and functions of various RNA modifications remain largely unknown. To provide transcriptome-wide landscapes of RNA modifications, we developed the RMBase v2.0 (http://rna.sysu.edu.cn/rmbase/ ), which is a comprehensive database that integrates epitranscriptome sequencing data for the exploration of post-transcriptional modifications of RNAs and their relationships with miRNA binding events, disease-related single-nucleotide polymorphisms (SNPs) and RNA-binding proteins (RBPs). RMBase v2.0 was expanded with ∼600 datasets and ∼1 397 000 modification sites from 47 studies among 13 species, which represents an approximately 10-fold expansion when compared with the previous release. It contains ∼1 373 000 N6-methyladenosines (m 6 A), ∼5400 N1-methyladenosines (m 1 A), ∼9600 pseudouridine (Ψ) modifications, ∼1000 5-methylcytosine (m 5 C) modifications, ∼5100 2′- O -methylations (2′- O -Me), and ∼2800 modifications of other modification types. Moreover, we built a new module called 'Motif' that provides the visualized logos and position weight matrices (PWMs) of the modification motifs. We also constructed a novel module termed 'modRBP' to study the relationships between RNA modifications and RBPs. Additionally, we developed a novel web-based tool named 'modMetagene' to plot the metagenes of RNA modification along a transcript model. This database will help researchers investigate the potential functions and mechanisms of RNA modifications.